Formulasi Sediaan Sabun Padat Dari Ekstrak Kulit Pisang Awak (Musa Balbisiana) Secara Maserasi - Rosa Mardiana; Yuniati Yuniati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Indonesia is the largest producer of bananas, along with the high productivity of bananas, the amount of banana peel waste also increases. When harvesting bananas, banana peels, stems and leaves (about 80%) are only removed without further processing. This is what causes the potential for banana peel waste to be large enough so that it is necessary to overcome the banana peel so that it has good value. The content in banana peels include carbohydrates, protein, fat, calcium, iron, phosphorus, vitamins B, C and C. Banana peel also has a cellulose content of 14.4%, an abundant amount, especially from banana peels, can be used as an efficient product. The method used in this study used the maceration method where the banana peel extract (Musa balbisiana) was made in the form of solid soap. which is heated and then the application of oil which is directly reacted with an alkaline solution at a temperature of 50˚C, so that a soap base is obtained. The solid soap preparation tests carried out in this study were organoleptic tests, pH tests and foam stability tests. The results of the evaluation of the preparation showed that the soap preparation was solid, there was no change in shape and odor, and had a pH that was in accordance with the standards for skin.